Evaluation of Serum Lipid Profile in Hypertensive Patients in one of Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: The objective of this study to evaluate serum lipid profile in hypertensive patients in one of tertiary care hospitalStudy Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Biochemistry and Physiology, Avicenna Medical College Lahore from March 2017 to January 2019.Materials and Methods: We selected 100 participants in which 70 hypertensive patients and 30 control normal subjects. We measured total cholesterol level (TG), Low density Lipoprotein (LDL), High density Lipoprotein (HDL) and Triglycerides in hypertensive patients and normal patients (Control). We also measured blood pressure (Systolic and Diastolic Pressure) for both groups. For measuring lipid profile (TG, HDL, LDL, and Total Cholesterol), we used Mirolab 300 and we used Merk kits of analysis the samples of both groups (Hypertensive Patients and Control Normal patients.Results: The mean of the blood pressure (systolic BP - 24 hours (mmHg) of test subject was 148.9 + 10.2 mmHg and for Control was 135.4 + 8.3 mmHg. And Diastolic blood pressure of the test patient was 97.6 + 6.3 mmHg. The total Cholesterol level was higher in test subject (hypertensive patients) as compare to control the total cholesterol in Test subject (hypertensive patients) was 240.8 ± 14.8 mg/dl and in control was 194.6 ± 32.5mg/dl. Result showed that triglyceride level was higher in hypertensive patient as compare to control. The total level of triglyceride in hypertensive patients was 170.3 ± 37.5 mg/dl and in control was 146.2 ± 34.2mg/dl. High density lipoprotein level in hypertensive patient was 59.6 ± 10.5 mg/dl and in control was 45.5 ± 11.2mg/dl. The result showed that HDL level is high in hypertensive patient. The low density lipoprotein in LDL was higher in hypertensive patient as compare to control. The mean value of LDL in hypertensive patient was 127.9 ± 23.5mg/dl and in control was 118.5± 20.5 mg/dl.Conclusion: High lipid profile is risk of cardiovascular disease and stroke so it should be treated as soon as possible and it means that abnormal lipid profile caused cardiovascular disease.